Influence of surface structure and tube material on the condensation heat transfer coefficient of propane on horizontal single tubes and in tube bundles - Kühl, Julius; Jander, Julius Hans; Piszko, Maximilian; Freitag, Detlef; Dietl, Jochen; El Hajal, Jean; Gotterbarm, Achim; Rausch, Michael Heinrich; Klein, Tobias; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2024)
The condensation heat transfer of propane on the outside of single horizontal tubes and in tube bundles was investigated by determining the condensation heat transfer coefficient αcond in a newly designed experimental setup. To study the influence of different surface structures and tube materials, experiments were conducted with a smooth tube, finned tubes with various fin densities and heights, and a high-performance condensation tube at vapor temperatures of 30 and 40 °C and varying heat flux densities. In addition, the influence of inundation on αcond was systematically investigated by varying the mass flow of liquid condensate at heat flux densities of 20 and 60 kW·m−2. The experimental setup was successfully validated using smooth tubes by a comparison of the resulting αcond with literature data and Nußelt's film theory. For the single copper tubes with fin densities from 19 to 48 fins per inch, αcond increased and was by factors of 9 to 21 larger than for the smooth tube at the same heat flux density. Investigations of the inundation effect have shown that the additional condensate can lead to an increasing condensate film thickness, which decreases αcond due to its increased thermal resistance, and/or can lead to turbulences in the condensate film, which increases αcond. The interplay of the two effects depends highly on the surface geometry. An increasing fin height always enhanced αcond, whereas a lower thermal conductivity of the tube material leads to a smaller αcond.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Condensation heat transfer; Finned tubes; Propane; Single tube; Tube bundle